Strategi Adaptasi Masyarakat Terpencil dalam Menghadapi Resesi Global dengan Kearifan Lokal - Sipin Putra; Rachmalina Soerachman; Setia Pranata (Journal of Religion and Social Transformation, 2023)
The purpose of this study is to describe the adaptation strategies of remote society in dealing with inflation and recession. How can purchasing power continue to grow even though the economy depends on natural products. The data in this study uses village economic data. Secondary economic data is processed together with qualitative data. This study uses a descriptive qualitative method. Researchers conducted FGDs with community groups, village government. Researchers conducted in-depth interviews with selected informants and made observations. Researchers doing data triangulation with participation observation. Data triangulation aims to make the data more objective, accurate and detailed according to people's living conditions. Local wisdom such as subsistence behavior is one of the adaptation strategies in dealing with inflation and recession. The wheels of the economy keep turning even though there are changes in consumption patterns. The ups and downs of purchasing power depend on harvest and natural conditions.